2022
DOI: 10.1039/d1nh00501d
|View full text |Cite
|
Sign up to set email alerts
|

Interlink among catalyst loading, transport and performance of proton exchange membrane fuel cells: a pore-scale study

Abstract: For the first time, a pore-scale model is developed to simulate the reactive transport of oxygen, protons, and electrons in the catalyst layer of PEM fuel cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Local mass transfer near the Pt catalyst, such as proton conduction and oxygen transport, and mass transfer across a CL, such as oxygen supply and liquid water removal, were investigated to some degree before. [41][42][43][44][84][85][86][87][88][89][90][91][92] However, studies on the emerged novel CLs such as nanowire, novel layered fiber arrangement, and ordered column array architectures are absent. Therefore, additional effort needs to be made to understand the transport phenomena in these new CLs to better guide their design for ultralow Pt loading PEMFCs.…”
Section: Accelerating Catalyst Layer Development For Ultralow Pt Load...mentioning
confidence: 99%
See 1 more Smart Citation
“…Local mass transfer near the Pt catalyst, such as proton conduction and oxygen transport, and mass transfer across a CL, such as oxygen supply and liquid water removal, were investigated to some degree before. [41][42][43][44][84][85][86][87][88][89][90][91][92] However, studies on the emerged novel CLs such as nanowire, novel layered fiber arrangement, and ordered column array architectures are absent. Therefore, additional effort needs to be made to understand the transport phenomena in these new CLs to better guide their design for ultralow Pt loading PEMFCs.…”
Section: Accelerating Catalyst Layer Development For Ultralow Pt Load...mentioning
confidence: 99%
“…These simulation methods have been employed to explore the electrochemical reactions on catalysts, evaluate catalyst activity, reveal local mass transfer characteristics, evaluate the three-phase boundaries for the reactions, explore two-phase flow in CLs, and evaluate CL performance. [19][20][21]27,41,44,[84][85][86][87]92 For example, Li et al 86 developed a pore-scale model based on the LB method to obtain the gas distribution, current density distribution, and voltage loss in CLs, by considering gas transport, proton transport, electron transport, and electrochemical reaction in this model. Fan et al 44,92 developed an oxygen transport model based on MD simulation to investigate the effect of ionomer film morphology on the local oxygen transport phenomena.…”
Section: Accelerating Catalyst Layer Development For Ultralow Pt Load...mentioning
confidence: 99%
“…[48,49] Therefore, virtual design and optimization of electrodes can only depend on synthetic microstructures generated by various stochastic algorithms and physical models. [50][51][52] Though stochastically synthetic microstructures have similar essential structural parameters, the intrinsic assumption in the algorithms limits the ability to generate realistic microstructures and therefore possibly leads to less realistic optimization results. Besides, the variables to be optimized are also limited, for example, grain size, positions and numbers, and are therefore unable to fully reflect the high complexity of real morphologies.…”
Section: Forward Design Using π Learningmentioning
confidence: 99%
“…Additionally, compared with VOF methods, porous structure reconstruction with LBM is usually easier. To date, LBM has been employed to study two-phase flow in the GDL, MPL, and CL of PEM fuel cells, , while few studies were reported for porous flow fields.…”
Section: Two-phase Flow Dynamicsmentioning
confidence: 99%